2012
DOI: 10.1002/chem.201200927
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐Enthalpy Correlations in Diels–Alder Reactions

Abstract: Woodward-Hoffmann (WH) rules provide strict symmetry selection rules: when they are obeyed, a reaction proceeds; when they are not obeyed, there is no reaction. However, the voluminous experimental literature provides ample evidence that strict compliance to symmetry requirements is not an obstacle for a concerted reaction to proceed, and therefore the idea has developed that it is enough to have a certain degree of the required symmetry to have reactivity. Here we provide quantitative evidence of that link, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…It should be noted that the nearest achiral structure is a mathematical construct which varies for each analyzed structure (for instance, for each Gly residue). Many correlations between the CSM or the CCM and chemical, physical, or biochemical properties that depend on symmetry or chirality have been successfully established; alternative approaches have been proposed by, e.g., Jamroz et al…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the nearest achiral structure is a mathematical construct which varies for each analyzed structure (for instance, for each Gly residue). Many correlations between the CSM or the CCM and chemical, physical, or biochemical properties that depend on symmetry or chirality have been successfully established; alternative approaches have been proposed by, e.g., Jamroz et al…”
Section: Methodsmentioning
confidence: 99%
“…Excellent correlations were found between the CSM and various physical and chemical properties . In particular, it has been shown that the variation of the CSM values along the IRC can serve as an indicator for the progress of a reaction. , …”
Section: Introductionmentioning
confidence: 97%
“…Likewise, NOE enhancements of H-4/H-15″, as well as H-2″/H-7″ and CH 3 -14″, indicated that H-4, H-2″, H-15″, and the side chain at C-6″ were on the other side. The trans -relationship between H-3 and H-4 complied with the Alder–Stein rule . From a biosynthetic point of view, compound 3 could be derived from curcumin and (−)-α-zingiberene via Diels–Alder [4 + 2] cycloaddition.…”
Section: Resultsmentioning
confidence: 62%
“…The transrelationship between H-3 and H-4 complied with the Alder− Stein rule. 16 From a biosynthetic point of view, compound 3 could be derived from curcumin and (−)-α-zingiberene via Diels−Alder [4 + 2] cycloaddition. (−)-α-Zingiberene is a major sesquiterpene in turmeric, and its absolute configuration had been assigned as 6″R,7″S by chemical synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%